2273. Neurosyphilis in Pacients With HIV Infection: Clinical Presentation of 94 Cases. (26th November 2018) - Rojas, Rodrigo; Wolff, Marcelo
Abstract: Background: Syphilis remains highly prevalent, particularly in men with HIV infection (HIV+), in whom atypical manifestations and neurosyphilis (NS) are frequent. NS may be asymptomatic and IM benzathine penicillin treatment is ineffective. Although ideal-but not practical-all cases of syphilis in HIV+ patients (patients) should have CSF study to rule out NS. The objective of this study was to quantify and characterize NS cases in HIV+ patients with syphilis. Methods: Retrospective study from 01-02-2013 to 04-30-2018 at Fundación Arriarán in Santiago, Chile of 618 coinfected patients with CSF study due to neurological, visual or auditory symptoms, or serum VDRL ≥ 1:32. Any positive VDRL titer in CSF was considered demonstrated NS (dNS) and isolated pleocytosis ≥ 20 cells/μL considered probable NS (pNS). Status of HIV infection, syphilis, CSF analysis, NS treatment, and follow-up were characterized. Results: NS was diagnosed in 94/618 patients (15.2%) with CSF study, (3 women), 80.8% were dNS and 19.2% pNS. Median age was 32 years (range 20–67); median CD4 cell count was 317 cells/μL (IQR of 188–473). In 41.5% NS was diagnosed at entry into care; syphilis was classified as primary in 2.1%, secondary in 22.3%, early–latent in 29.8% and late latent in 45.8%. Most cases of NS (84%) were neurologically asymptomatics (88.8% in pNS). Median CSF leukocytes in dNS was 5 cells/μL (range 0–338), and in pNS 31 cells/μL (range 16–90). Treatment was with IV ceftriaxone in 57/94 (60.6%), and in 39.4% with IV sodium penicillin. Follow-up data with serum VDRL at 3, 6 and 12 months were obtained in 44/94 (41.4%), 37.6% and 24.4% of patients respectively, who presented a decrease of 2-fold serum VDRL in 35/44 (79.5%), 82.5% and 92.3% with data, according to baseline, respectively. Conclusion: NS is an important complication of syphilis in HIV+ patients; and it should be suspected and actively investigated throughout their care given the high rate of asymptomatic status, even in NSd. Positivity of VDRL in CSF is associated with more symptoms. Ceftriaxone is an alternative therapy, but that requires larger and longer prospective studies for confirmation. The decrease of 2-fold serum VDRL in 6 months may predict treatment success. The role of CSF study post treatment to evaluate this outcome and the criteria for cure have not been well established. Disclosures: All authors: No reported disclosures.